Juridical Construction of Data Accuracy Principles in Personal Data Protection Governance: A Comparative Analysis of Indonesia and Singapore - Seroja Rizki Amelia; Sidi Ahyar Wiraguna (Dinasti Research, 2026)
The transformation of personal information into strategic commodities within digital ecosystems has elevated data quality governance beyond mere administrative concerns to a constitutional imperative. This study examines the juridical construction of the accuracy principle within Indonesia's Law Number 27 of 2022 on Personal Data Protection (PDP Law) and contrasts this with Singapore's Personal Data Protection Act 2012 (PDPA). Using normative-comparative legal research enriched with statutory, conceptual, and comparative functionalism approaches, this research evaluates whether Indonesia's regulatory framework provides sufficient operational certainty for data controllers and adequate protection for data subjects. The analysis reveals that while Article 16 of the PDP Law nominally mandates accuracy, completeness, and consistency, the provision remains declarative and lacks definitional precision, temporal updating mechanisms, and clear liability parameters. Conversely, Singapore's PDPA operationalizes accuracy through the Accuracy Obligation and Correction Obligation, enforced by an independent Personal Data Protection Commission (PDPC) with investigative and sanctioning powers. This study proposes a juridical reconstruction of Indonesia's accuracy principle through periodic data audits, effective correction protocols, risk-based governance calibration, and the establishment of an independent supervisory authority with quasi-judicial competencies.